KETERBACAAN PETA ANDA DI SINI (ADS) KAMPUS UNIVERSITAS PENDIDIKAN INDONESIA - Nurfauziah, Sih Aulia (Jurnal Pendidikan Geografi Gea, 2015)
Anda di Sini (ADS) map is a tool that showed spatial structures of specific place, therefore the ADS map have been used at many places as guidepoint for reader to explore the place. Generally, ADS map is containing mark about location map of (at once the location of readers) using the arrow with the inscription ‘Anda di Sini’ on it, or using striking color. As another map, the ADS map contains information of direction as the key of orientation for reader to interpret the map. Therefore the location of the ADS map must be compatible with reader orientation, that means the ADS map face the reader as same as a mirror. The mirror position can decrease distractions of reader’s cognitive navigation that caused by complex stimuli. In 2014, Universitas Pendidikan Indonesia (UPI) placed two ADS maps at opposite of  Museum Pendidikan Building and at front of Geugeut-Winda Building. But both of them have incompatible position with reader orientation which causing the mental rotation of maps is not equal to zero and the reader is hard to interpret the ADS maps. The purpose of this paper is to examine the ADS maps of UPI by exploring theories about map-reading activity and used survey to collect the data.Keywords: ADS map, direction, orientation, mental rotation